2013
DOI: 10.1002/pdi.1781
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic streaming in type 1 diabetes: implications for intervention?

Abstract: Evidence exists that mean glycaemia in individuals with type 1 diabetes may remain remarkably constant (glycaemic ‘streaming’ or ‘tracking’). We have re‐examined this in a group of type 1 patients, to explore whether any subgroups may be more or less amenable to glycaemic improvement.We made a retrospective analysis between 2003 and 2007 of 181 people with type 1 diabetes. Basic demographic information, and sequential glycated haemoglobin (HbA1c) levels during the five‐year follow‐up period (2003–2007), were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Second, the benefits of addressing HbA 1c after the first 5 years should be explored. It has been suggested that efforts would be better directed at risk factors other than HbA 1c in individuals with established type 1 diabetes [13]. However, such an approach may result in loss of the tracking phenomenon and deterioration in HbA 1c so this needs to be carefully explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the benefits of addressing HbA 1c after the first 5 years should be explored. It has been suggested that efforts would be better directed at risk factors other than HbA 1c in individuals with established type 1 diabetes [13]. However, such an approach may result in loss of the tracking phenomenon and deterioration in HbA 1c so this needs to be carefully explored.…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, previous reports [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] have largely examined individuals with pre-existing type 1 diabetes (i.e. not from the time of diagnosis).…”
Section: Introductionmentioning
confidence: 99%
“…In the first year following treatment with insulin, there were significant improvements in glycaemic control, with a mean (SD) HbA 1c of 61 (21.9) mmol/mol [7.7 (2.0) %] accompanied by significant increases in BMI, with no further improvement in the years thereafter. Other work has also reported that glycaemic control tends to remain constant (glycaemic streaming), emphasising the importance of maximising gains soon after diagnosis [9]. Conversely, the lack of further improvement in glycaemic control in years 2-5 in this study was consistent with findings from the National Diabetes Audit, which indicated that less than one-third of the population with T1D achieved glycaemic target of <58 mmol/mol (<7.5%) in 2016/2017 [10].…”
Section: Discussionmentioning
confidence: 99%
“…These have consistently shown that DAFNE students have much lower rates of severe hypoglycaemia than the DCCT cohort, yet almost always manage to make significant reductions in average HbA 1c (Fig. 1) [5][6][7][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Yet, although students on DAFNE are asked to aim for a target of 45-55 mmol/mol (6.0-7.0%), they in fact attain a mean HbA 1c concentration of~68 mmol/mol [~8.4% (Fig 1)].…”
Section: Introductionmentioning
confidence: 99%